(untitled) (International Journal of Engineering and Computer Science, 2016)
v Orthogonal frequency division multiplexing (OFDM) is a popular modulation/multiplexing scheme offers high data rates It is considered as multicarrier transmission scheme supports future generation wireless as well as wire line communication systems.. OFDM frequently suffers from high Peak to Average Power Ratio (PAPR) which eventually increases the Analogue to Digital and Digital to Analogue convertors complexity levels and reduces HPA (RF) efficiency. Various Peak to average power ratio (PAPR) reduction schemes have been proposed in the past and companding is the popular PAPR reduction which is inserted after modulation in the OFDM system. Although companding scheme provides better results but simultaneously its presence as extra operation increases the bit error rate. In this paper a novel piecewise linear companding scheme is implemented to reduce the PAPR impact and control the companding distortion in the OFDM system. The piecewise linear companding scheme reduces the peak to average power ratio by clipping the amplitudes over the companded peak amplitude and compensate the power by linearly transform the signal amplitudes which are close to the companded peak amplitude. Finally the simulation result yields the better spectral efficiency and batter BER performance while mitigating the companding distortion better way the PAPR is reduced in accurate way.